RESPONS PERTUMBUHAN KEMANGI (Ocimum sanctum L) TERHADAP PEMBERIAN PUPUK ORGANIK DAN ANORGANIK - Sendy F. Gigir; Jenny J. Rondonuwu; Wiesje J.N. Kumolontang; Rafli I. Kawulusan (COCOS, 2014)
Abstract The study aims to look at and figure out how the basil plant responses to organic and inorganic fertilizer application on plant growth and development . Also to identify the needs of macro nutrients which provides good leverage for the growth and production of basil plants . The Methods of study was conducted by using a randomized block design with 6 treatment, A control with no fertilizer application , treatment B with organic matter ( manure ) and fertilizer N ( urea ) , P ( SP - 36 ) , and K ( KCL ) ; C treatment with N fertilizer ( urea ) , P ( SP - 36 ) , K ( KCl ) ; D treatment by administering organic matter ( manure ) and fertilizer P ( SP - 36 ) , K ( KCl ) ; Treatment of E with the provision of organic matter ( manure ) and fertilizer N ( urea ) , K ( KCl ) ; and treatment by administering F organic material ( manure ) , N fertilizer ( urea ) fertilizer P ( SP - 36 ) . This treatment was repeated 4 times . Fertilization treatment given compiled using minus one test , by making combinations between fertilizing compost , fertilizer N, P , and K by removing one of the elements of the four elements. The variables measured were plant height , number of branches and fresh weight . The results showed a response to the treatment plant fertilizer application . Macro nutrients nitrogen effect on plant growth Keywords : basil , Inorganic Fertilizer , Organic Fertilizer , Fertilizer Influence